Lectotypification of Saxifraga yuparensis Nosaka (Saxifragaceae) - Tamura, Saya; Takahashi, Hideki; Shutoh, Kohtaroh; Sato, Ken; Sato, Hiroyuki; Shimamura, Takashi; Nakamura, Koh (Phytotaxa, 2022)
We discussed the typification of the name Saxifraga yuparensis applicable to an alpine plant described from Hokkaido, northern Japan. The holotype is not found in the cited herbarium and other herbaria related to Nosaka. No isotypes or paratypes were cited in its protologue, and no other uncited specimens are unambiguously deduced to have been used by Nosaka when describing the species and do not comprise the original material (Art. 9.4 of the Botanical Code). Therefore, an illustration (Fig. 11 in Nosaka 1974) published as part of the protologue is the only original material that can be chosen in lectotype designation in conformity with Art. 9.12. The illustration is here designated as the lectotype for the name.